Giovanni of Montecorvino in Khanbaliq: Literary and Cultural Implications of a Lost Mongolian Bible Translation - Amartuvshin, Dulguunsaran (The Chinggisid History and Heritage Journal, 2026)
This study reviews Giovanni of Montecorvino's lost Mongolian Bible translation based on remaining evidences, and discusses the factors that could have led to its disappearance, and its possible significance towards Mongolian literary history, linguistics, and translation studies. The research analyzes Giovanni's work by drawing on missionary letters, subsequent historical records, and comparative assessments of existing Mongolian Bible translations. In Khanbaliq, Giovanni completed the translation of the New Testament and the Psalter into Mongolian in the early fourteenth century, making it the earliest recorded case of a Mongolian Bible translation. Therefore, it is still a significant literary work for researchers to be aware of. Its potential historical, linguistic, and literary influence goes beyond missionary history, as it can portray early Mongolian literary culture, medieval translation methods, and cross-cultural exchange under the Mongol Empire.